2023
DOI: 10.1136/bmj.p3
|View full text |Cite
|
Sign up to set email alerts
|

How are covid-19 symptoms changing?

Abstract: How are covid-19 symptoms changing?With new variants and a changing landscape of vaccination and immunity, what do the symptoms of covid-19-and our understanding of them-now look like? Mun-Keat Looi reports Mun-Keat Looi international features editorHow have covid symptoms changed since the start of the pandemic?In the short space of a few years we've seen surprising changes in the way covid-19 presents. At the start of the pandemic the first commonly reported symptoms were loss of smell and taste, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 1 publication
2
25
0
Order By: Relevance
“…[4][5][6] However, how to predict who is at risk and what the precise source of long-COVID is has not been clear to date in any respect. 3 This article thus attempted to update what we know in this regard, including possible determinants that have only recently been discussed such as the role of a possible dysregulated immune system, 7 and inflammation linked pathologies within the nervous system, the cardiovascular, and the gastrointestinal or metabolic systems in vulnerable post-acute COVID-19 survivors. 6 This report also focuses on what researchers currently conclude about long COVID-19 health attributes, and in particular any age associated insights and possible remediation factors, as reported in the PUBMED database and others in early 2023.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, how to predict who is at risk and what the precise source of long-COVID is has not been clear to date in any respect. 3 This article thus attempted to update what we know in this regard, including possible determinants that have only recently been discussed such as the role of a possible dysregulated immune system, 7 and inflammation linked pathologies within the nervous system, the cardiovascular, and the gastrointestinal or metabolic systems in vulnerable post-acute COVID-19 survivors. 6 This report also focuses on what researchers currently conclude about long COVID-19 health attributes, and in particular any age associated insights and possible remediation factors, as reported in the PUBMED database and others in early 2023.…”
Section: Introductionmentioning
confidence: 99%
“…However, the research and development (R&D) of these drugs and vaccines have focused mainly on the spike protein of the virus, but as observed, the virus mutates—evident from the variants that were circulating during the pandemic—which potentially may eventually render them less effective in the long term. Clinicians are overwhelmed by a complete change in viral symptoms every time there is a new strain in circulation [ 3 , 4 ]. Mathematical modeling has been helpful to only an extent [ 5 , 6 ], even with a much more extensive understanding of risk factors and prognosis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Omicron infections are mainly restricted to the upper respiratory tract and are thus generally associated with mild disease. 3,4 However, Omicron infections may still result in severe disease in immunocompromized patients or those with pre-existing comorbidities, which substantially contributes to hospitalization rates and general disease burden. 5,6 Several observational studies reported a high incidence of Omicron vaccine-breakthrough infections and reinfections.…”
Section: Introductionmentioning
confidence: 99%